2020
DOI: 10.1177/0734371x19897753
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Well-Being Among Public Employees With Disabilities: The Roles of Disability-Inclusive Human Resource Practices, Job Resources, and Public Service Motivation

Abstract: Regardless of their disabilities, employees with disabilities can contribute to the performance of public organizations. Our research purpose is to investigate how and when disability-inclusive human resource (HR) practices nurture the well-being of employees with disabilities in the public sector. Participants for this study consisted of employees with disabilities from departments and wards (grassroot-level governments) under the district-level governments in Ho Chi Minh City, Vietnam. Our results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…Employment is an integral part of life that provides individuals with a sense of financial security [ 1 ], determines self-esteem and social recognition [ 2 ], and has an impact on one’s wellbeing [ 3 ]. We now observe an expanding literature on the benefits of creating employment opportunities for people with disabilities [ 4 , 5 , 6 ], yet such individuals still experience a disproportionately high level of job insecurity, underemployment, and unemployment compared to workers without disabilities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Employment is an integral part of life that provides individuals with a sense of financial security [ 1 ], determines self-esteem and social recognition [ 2 ], and has an impact on one’s wellbeing [ 3 ]. We now observe an expanding literature on the benefits of creating employment opportunities for people with disabilities [ 4 , 5 , 6 ], yet such individuals still experience a disproportionately high level of job insecurity, underemployment, and unemployment compared to workers without disabilities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This means that even though an article uses the term HRM practices, the practices were only categorized as HRM if they were connected to formal policies. Thus, HRM practices are the workplace's operationalization of diversity policies, in terms of what the workplace should offer PWD, like a buddy system (Bartram et al 2021;Tuan et al 2021), flexible schedules, benefit packages, and personal development opportunities (Habeck et al 2010;Tuan et al 2021), and in terms of who needs to get involved, typically occupational physicians or others from the company's health service (Haafkens et al 2011;Habeck et al 2010). Also, seeking knowledge and aiming for best practices in employment of PWD (Bartram et al 2021;Chordiya 2022) are examples of HRM practices.…”
Section: Workplace Practicesmentioning
confidence: 99%
“…(Bartram et al 2021;Blonk et al 2020;Carrier 2007;Cavanagh et al 2021;Meacham et al 2017a;Meacham et al 2017b;Miller et al 2014;Trezzini et al 2021) and 10 are quantitative (Eissenstat, Lee & Hong 2022;Filary & Pernice 2006;Flores et al 2021;Gray, Morgan & Hollingsworth. 2014;Lyubykh et al 2020;Novak & Rogan 2010;Sanclemente et al 2022;Tuan et al 2021;Zhu et al 2019;Schur et al 2009). Job satisfaction, well-being, and thriving at work are the most recurrent outcomes within this category.…”
Section: The Link Between Workplace Practices and Employment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some scholars have investigated how HRM practices can improve public personnel well-being. For example, Tuan et al (2020) found that disability inclusive HR practice can foster well-being of public employees with disabilities. Comparing the emotional well-being of public vs private sector employees, Lahat and Ofek (2020) argued that HR environment (including level of discretion, employee participation and social relationship) is responsible for higher levels of emotional well-being among public sector employees.…”
Section: Hrm and Public Personnel Well-beingmentioning
confidence: 99%